Evolution of attack in handball when playing 7 vs. 6 with empty goal between 2020 and 2023: coaches’ perception vs. observational results - Prudente, João Nunes; Cardoso, Américo Ramos; Rodrigues, Ana José; Mendes, João N.; Fernando, Catarina; Lopes, Helder; Trejo-Silva, Alejandro; Sousa, Duarte Filipe (Frontiers in Sports and Active Living, 2024)
Introduction Recently, several studies on the 7 vs. 6 “empty goal” (EG) in handball have produced different and even contradictory results. The aim of the present study was to investigate the behavior of teams and players in the 7 vs. 6 EG attack in the European (Euro) and World Championships (WCh) between 2020 and 2023 and characterize the coaches’ perceptions. Methods A mixed-methods approach was used, consisting of the following: (i) an observational methodology and instrument developed and validated to collect observational data on player and team behavior; and (ii) a developed and validated questionnaire to coaches on their perceptions of the 7 vs. 6 game. Observational data were collected during the Euro 2020 and 2022 games (n = 62) and the WCh 2021 and 2023 games (n = 70). A total of 132 games and 391 situations of 7 vs. 6 attacking sequences were observed. In total, 156 coaches participated (146 men), with a mean age 42.33 ± 11.87 years, 19 nationalities, and with 12.77 ± 9.45 years of experience. Results and discussion The choice of 7 vs. 6 offensive play was mostly made in the second half (>73%). The effectiveness of 7 vs. 6 offensive sequences was higher in the top six teams than in the team's ranked 7th to 12th (Euro 2020 51.6%–50.0%; WCh 2021 52.0%–50.0%; Euro 2022 53.1%–41.7%; WCh 2023 50.0%–43.8%). Some patterns of association were found (p < 0.05 and with values >±1.96): (i) scoring a goal with a breakthrough shot was significantly associated with the effectiveness of the 7 vs. 6 attack (Euro 2020 2.61; WCh 2021 2.87; Euro 2022 2.68; WCh 2023 2.32); (ii) teams in the top six significantly used 7 vs. 6 when they were winning (Euro 2020 2.17; WCh 2021 3.52; Euro 2022 5.88; WCh 2023 2.54); and (iii) teams in the bottom six used it when they were losing by at least four goals (Euro 2020 7.56; Euro 2022 6.64; WCh 2023 4.37) or when they were winning by four goals or more (WCh 2021 2.58). Coaches that agree with the possibility of playing 7 vs. 6 (74.4%), rarely or never do so (55.6%) because it brings little or no advantage (52.6%). The results of the analysis confirmed the perception of the coaches, the low use of 7 vs. 6, the low advantage associated with it, and the influence of the result and the moment of the game on its use.